2009
DOI: 10.1097/01.ogx.0000359274.99100.5a
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Second Trimester Screen Positive Pregnancies at Increased Risk for Congenital Heart Defects

Abstract: A number of studies have reported an association between low concentrations of serum folate and preterm birth. Folate supplementation during pregnancy increased the length of pregnancy in some but not all clinical trials. This cohort study investigated whether preconceptional folate supplementation (as ascertained by patient questionnaire in the first trimester of pregnancy) lowers the risk of spontaneous preterm birth. The investigators analyzed data collected from a cohort of 34,480 low-risk singleton pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…Taking into account the fact that very few referral centres have the facilities to provide detailed cardiac scans, we should be careful about the interpretation of this screening test's results and the information we give to the parents. Most of the instances of CHD are currently still diagnosed in the second or even the beginning of the third trimester 34 and decisions for management are more difficult at this point. It is very important to find noninvasive diagnostic tests that will place safely a fetus from the low-risk group for CHD into a high-risk group or the opposite during the first trimester so that the therapeutic approach and the decision-making will occur as soon as possible, minimising maternal and fetal morbidity.…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account the fact that very few referral centres have the facilities to provide detailed cardiac scans, we should be careful about the interpretation of this screening test's results and the information we give to the parents. Most of the instances of CHD are currently still diagnosed in the second or even the beginning of the third trimester 34 and decisions for management are more difficult at this point. It is very important to find noninvasive diagnostic tests that will place safely a fetus from the low-risk group for CHD into a high-risk group or the opposite during the first trimester so that the therapeutic approach and the decision-making will occur as soon as possible, minimising maternal and fetal morbidity.…”
Section: Resultsmentioning
confidence: 99%
“…Using independent samples, both studies found that abnormally high or low hCG levels were strongly associated with an increased risk for CHDs in screen positive pregnancies. In addition, our most recent study observed a positively predictive relationship between low AFP levels and an increased risk for CHDs in screen positive pregnancies (Jelliffe‐Pawlowski et al , 2009).…”
Section: Introductionmentioning
confidence: 85%
“…Although much has been learned with respect to the predictive relationship between first trimester nuchal translucency (NT) measurement and congenital heart defects (CHDs) (Simpson et al , 2007; Wald et al , 2008), few studies have examined the relationship between typically collected prenatal serum biomarkers and CHDs (Souter et al , 2002; Jelliffe‐Pawlowski et al , 2009). Identification of additional predictive biomarker–CHD relationships has the potential to better CHD prenatal detection rates in instances where a first trimester NT measurement was not performed and potentially for affected pregnancies in which NT screening was normal (estimated to be between 44 and 86% of all CHDs) (Westin et al , 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the California Prenatal Screening Program includes follow-up diagnostic services and receives diagnostic outcome reports of these services, the Program has been aware that many other structural abnormalities and pregnancy findings are detected among the screen-positive population. Major fetal abnormalities associated with screen-positive status for SLOS have been previously reported (Craig et al, 2007) as well as increased risk of cardiac defects among fetuses of all screen-positive women (Jelliffe-Pawlowski et al, 2009). Significant associations between several maternal serum markers and an increased risk for multicystic dysplastic kidney, two-vessel cord and hydrocele were demonstrated in participants of the FASTER trial (Hoffman et al, 2008).…”
Section: Discussionmentioning
confidence: 97%